2019
DOI: 10.1002/smi.2897
|View full text |Cite
|
Sign up to set email alerts
|

Burnout is associated with a depressive interpretation style

Abstract: The aim of this 188‐participant study (65% female; mean age = 40.31) was to examine whether burnout and depression are associated with similar interpretation biases in the processing of emotional information. Burnout symptoms were assessed with the Maslach Burnout Inventory‐General Survey and depressive symptoms with the 9‐item depression module of the Patient Health Questionnaire. Interpretation bias toward emotional information was examined using an amended version of the Word‐Sentence Association Paradigm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
3
6
0
Order By: Relevance
“…Importantly, the association remained statistically significant controlling not only for pretest mood but also for test performance, suggesting that occupational depression darkens individuals’ view of the task undertaken in a way that is partly independent of their ability to handle the task in question. These results are in keeping with the well-established finding that depression involves a negative filter in the processing of information ( Bianchi et al, 2018 ; Bianchi and da Silva Nogueira, 2019 ; LeMoult and Gotlib, 2019 ). In addition, we found that individuals evaluating the task as “frustrating” and “discouraging” were also those who exhibited the highest levels of depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, the association remained statistically significant controlling not only for pretest mood but also for test performance, suggesting that occupational depression darkens individuals’ view of the task undertaken in a way that is partly independent of their ability to handle the task in question. These results are in keeping with the well-established finding that depression involves a negative filter in the processing of information ( Bianchi et al, 2018 ; Bianchi and da Silva Nogueira, 2019 ; LeMoult and Gotlib, 2019 ). In addition, we found that individuals evaluating the task as “frustrating” and “discouraging” were also those who exhibited the highest levels of depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…A key aspect of depressive symptomatology lies in altered cognitive functioning, in terms of (a) processing efficacy and (b) information selection and construction. Regarding information selection and construction, there is ample evidence that depressive symptoms are associated with so-called biases in favor of “negative” information (or to the detriment of “positive” information) at the levels of attention, interpretation, and memory ( Everaert et al, 2014 ; Bianchi and Laurent, 2015 ; Bianchi and Schonfeld, 2016 ; Bianchi et al, 2018 ; Bianchi and da Silva Nogueira, 2019 ; LeMoult and Gotlib, 2019 ). Regarding processing efficacy, depression has been associated with pervasive impairment, for instance, at the level of executive functions ( Snyder, 2013 ; Rock et al, 2014 ; Ahern and Semkovska, 2017 ; Semkovska et al, 2019 ; Pettersson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results also indicated that exhaustion is strongly associated with both the affective-cognitive and the somatic subscale of the PHQ-9. These results are consistent with the finding that burnout involves a depressive cognitive style (Bianchi & da Silva Nogueira, 2019;Bianchi, Laurent, Schonfeld, Bietti, & Mayor, 2020;Bianchi, Laurent, Schonfeld, Verkuilen, & Berna, 2018;Golkar et al, 2014). On a different note, our results question Maslach and Leiter's (2016) argument that the "high correspondence of burnout and depression" is driven by betweenscale overlap at the level of fatigue-related items (p. 107).…”
Section: Conditionsupporting
confidence: 90%
“…From an empirical standpoint, burnout has been found to overlap with depression in terms of (a) basic etiology and symptoms (e.g., Ahola et al, 2014; Bianchi, Schonfeld, & Verkuilen, 2020; Schonfeld et al, 2019a, 2019b; Wurm et al, 2016); (b) behaviorally assessed cognitive alterations in the processing of emotional stimuli (e.g., attention, interpretation, and memory biases; Bianchi & da Silva Nogueira, 2019; Bianchi & Laurent, 2015; Bianchi, Laurent, et al, 2020); (c) dispositional correlates and risk factors, such as neuroticism, borderline personality traits, histories of anxiety and depressive disorders, histories of stressful and traumatic life events, and a pessimistic attributional style (e.g., Bianchi, 2018; Bianchi, Rolland, & Salgado, 2018; Bianchi & Schonfeld, 2016; Mather et al, 2014; Prins et al, 2019; Rössler et al, 2015; Rotenstein et al, 2021; Swider & Zimmerman, 2010); (d) the extent to which individuals attribute symptoms to workplace stress (Bianchi & Brisson, 2019); (e) treatments used, such as antidepressant medication (e.g., Ahola et al, 2007; Leiter et al, 2013; Madsen et al, 2015); and (f) somatic outcomes, including cardiovascular disease and diabetes (e.g., Carney & Freedland, 2017; Hare et al, 2014; Melamed et al, 2006; Mezuk et al, 2008; Toker et al, 2012). Although early factor analytic studies of burnout–depression overlap concluded that burnout is distinct from depression (Bakker et al, 2000; Leiter & Durup, 1994), methodological problems (e.g., overlooking of divergent findings, treatment of ordinal data as interval, model fit issues, questionable exclusion of depressive symptom items) limit the applicability of those conclusions (see Schonfeld et al, 2019a, 2019b).…”
Section: Depression and Burnoutmentioning
confidence: 99%